Intelligent Baby Box Based on IoT to Observe Room Temperature and Baby Crying - Sasmoko, Dani; Bachtiar, Dzyo (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 9, No. 3 December 2018DO - 10.24843/LKJITI.2018.v09.i03.p01, 2018)
Internet of Things (IoT) connects a global infrastructure in communities so they can take benefit of advanced services, by connecting objects (things) both physical and virtual with the Internet so that objects can communicate each other. The object of this study is a baby box to control the baby’s condition. When the baby cries too long it may cause Baby Distressed Tantrum which is the feeling of being depressed in the baby because they feel ignored. If this happens for a long time will endanger the baby's health as it is related to respiratory function and cardiac performance. The function of the baby box is to observe a baby when left without supervision. It will enable users to know if the baby is sleeping, awake or crying. Leaving a crying baby too long may have a negative effect. By applying the Internet of Things (IoT) in the design of an intelligent a baby box will help the parents and babysitter in controlling the baby if they have other activities to do. The baby box monitoring system has a dht11 temperature and humidity sensor, and a noise sensor to detect the baby crying. An esp8266 module on Wemos d1 will send data to an android smartphone and notify the user by sound or vibration.